SELF-CLEANING GLASS BASED ON ACID-TREATED TiO2 FILMS WITH PALMITIC ACID AS MODEL POLLUTANT - Nurul Hidayat Aprilita; Indriana Kartini; Sofy Herawati Ratnaningtyas (Universitas Gadjah Mada, 2008)
Preparation and characterization of self-cleaning glass based on acid-treated TiO2 films as well as evaluation on their self-cleaning properties have been carried out. Palmitic acid photodegradation was used as model pollutant. Acid-treated TiO2 powders were deposited on glass surface by using spraying technique. The XRD results showed that acid-treated TiO2 film exhibited decreased anatase crystalline size. The corresponding SEM images showed porous surface morphology. Layer densification was observed as the film thickness increased. TiO2 photocatalytic activity increased as the length of UV radiation increased. Best results were obtained at experimental condition of 35 hours UV radiation time. It is also observed that the thickness of TiO2 layers influenced the efficiency of palmitic acid photodegradation. The film with 1.661 µm thick TiO2 layers and 6.933 mg weight (0.7164 mg/cm2) could degrade 97.54 % mg palmitic acid/cm2 thin film.